(untitled) (Research, Society and Development, 2020)
Intensive Care Units (ICUs) increasingly admit patients diagnosed with neurological disorders. The proven brain injury from trauma is considered a global health problem. The mortality of these patients is directly related to clinical severity and dependence on specialized care. Thus, it is necessary to elucidate the profile of patients admitted to the ICU diagnosed with a neurological disorder, in order to organize health interventions and act in the prevention of the triggering factors of these diseases, contributing to the systematization of nursing care in this sector. The presente study aimed to characterize the profile of patients admitted to the ICU with the diagnosis of neurological damage. For this, a quantitative research was carried out, based on the analysis of the medical records of users admitted to the ICU of the Regional Hospital Tarcísio de Vasconcelos Maia located in the city of Mossoró-RN. After analyzing the data, it was found that Cranioencephalic Trauma (TBI) was the most prevalente reason for hospitalization in the hospital’s emergency room and neurological damage was the most prevalente reason for admission to the ICU. Most of the patients with neurological disorders were men, with na average age of 47 years old. Regarding the outcome, 77.50% of users with neurological disorders died, with 37.71% diagnosed with TBI. The characteristics found in the research may contribute to the elaboration of care strategies to offer quality nursing care to patients diagnosed with neurological disorders, optimizing the care provided and adequate support.